Confirming the Presence of Neurapraxia and Its Potential for Immediate Reversal by Novel Diagnostic and Therapeutic Ultrasound-Guided Hydrodissection Using 5% Dextrose in Water Without Local Anesthetics: Application in a Case of Acute Radial Nerve Palsy - Ho Won Lee; Jihyo Hwang; Chanwool Park; Minjae Lee; Yonghyun Yoon; Yeui-Seok Seo; Hyemi Yu; Rowook Park; Jaehyun Shim; Junhyuk Ann; Daniel Chiung-Jui Su; Teinny Suryadi; et al. (Diagnostics)
Background and Clinical Significance: Radial nerve palsy typically presents as wrist drop due to nerve compression, with conventional management often yielding prolonged recovery. We report a case where ultrasound-guided hydrodissection (HD) with 5% dextrose in water (D5W) achieved immediate functional restoration, suggesting neurapraxia as the underlying pathology. Case Presentation: A 54-year-old diabetic female presented with acute left wrist drop without trauma. Examination confirmed radial nerve palsy (MRC grade 0 wrist extension), while radiographs ruled out structural causes. Ultrasound revealed fascicular swelling at the spiral groove. Under real-time guidance, 50 mL D5W (no local anesthetic) was injected to hydrodissect the radial nerve. Immediate post-procedure assessment showed restored wrist extension (medical research council (MRC) grade 4+). At one- and three-month follow-ups, the patient maintained complete resolution of symptoms and normal function. Conclusions: This case highlights two key findings: (1) HD with D5W can serve as both a diagnostic tool (confirming reversible neurapraxia through immediate response) and therapeutic intervention, and (2) early HD may circumvent prolonged disability associated with conservative management. The absence of electrodiagnostic studies limits objective severity assessment, though ultrasound localized the lesion. While promising, these observations require validation through controlled trials comparing HD to standard care, particularly in diabetic patients with heightened compression susceptibility. Technical considerations—including optimal injectate volume and the role of adjuvant therapies—warrant further investigation. US-guided HD with D5W emerges as a minimally invasive, surgery-sparing option for acute compressive radial neuropathies, with potential to redefine treatment paradigms when applied at symptom onset.